RFM Segmentation Analysis as the Base of The Company Marketing Strategy: Case Study of Medical Device Company PT. Abc - Marc Giulio Richard; Jerry Heikal (CV. ULIL ALBAB CORP, 2024)
Medical Device Companies Play Significant Roles As Partners For Healthcare Institutions Such As Hospitals, Clinics, And Laboratories. They Are Crucial In Helping And Supporting Healthcare Institutions Improving The Quality Of Life Of The Human Population In Modern Times. In The Field Of Marketing, Medical Device Companies Face Increasing Challenge In Sales Performance And Profits Pressure, As Well As Maintaining Customer Loyalty. Medical Device Customers Usually Decide Purchases Influenced Not Only By The Selling Price, But Also By The Quality Of The Product, The Compatibility With Other Brands, The Ease Of Use, The After Sales Service, And Many Other Factors. Based On These Conditions, Medical Device Purchasing Patterns In Indonesia Become Unpredictable, And It Is Difficult To Increase Sales And Profits. One Effort That Medical Device Business Players Can Make Is To Carry Out Sales Promotions Based On Customer Segmentation. Customer Segmentation In Medical Device Companies Can Be Done Using Customer Segmentation Methods, Such As Recency Frequency Monetary (Rfm) Analysis. This Method Allows Companies To Group Customers Based On Purchasing Patterns Of The Medical Device Products, Thereby Allowing Companies To Prioritize Time, Energy, And Resources Into Each Different Segment Correctly And Strategically. The Segmentation Results Found Eight Customer Segments Of Pt Abc: Vip, Loyal, New Potential, Potential Vip, At Risk Customer, Lost Gold, Dormant Customer, Non-Core. Proposed Strategies Include Personalized Promotions For Different Customer Segments, Such As Promoting Vip & Loyal Customers In Pt Abs’s Social Media, Offer Bundled Pricing To New Potential And Potential Vip Customers, And Launch a New Economical Product For Dormant Customers, Lost Gold, And At-Risk Customers. These Strategies Aim To Enhance Customer Engagement, Loyalty, And Satisfaction Through Segmented Marketing And Personalized Promotions.